Market Access Challenges and Solutions in Cell and Gene Therapy in The Netherlands - Rimma Velikanova; Sharon Wolters; Hinko S. Hofstra; Maarten J. Postma; Cornelis Boersma (Journal of Market Access & Health Policy)
With the increasing pipeline of cell and gene therapies (CGTs) and the expected surge in the number of approvals, understanding the market access landscape becomes crucial for timely patient access. This study evaluates the challenges Dutch stakeholders encounter in CGT market access, offering insights for improving time-to-patient access. A traditional literature review was conducted to identify market access challenges and solutions for CGTs. Based on the findings, participants for semi-structured interviews, designed using an interview guide adapted to the Dutch context, were selected to capture diverse perspectives on market access. This review included 124 relevant articles out of 2449, covering several aspects of market access of CGTs. Subsequently, interviews with 16 stakeholders from academia, patient advocacy groups, manufacturers, health insurers, payers, hospital pharmacists, healthcare practitioners, and the Association of Innovative Medicines were conducted. Stakeholders identified challenges and proposed solutions for reimbursement package management, clinical trials, health economics, payment models, and procedural and organisational aspects. Thematic analysis revealed unique country-specific challenges and solutions in the Netherlands. This research provides insights into these challenges and potential solutions, emphasising the need for collaborative efforts among stakeholders to develop practical and multidisciplinary measures to improve the market access landscape for CGTs in the country.